Implementation Of Volleyball Extracurricular Activities In Fostering Discipline And Mutual Cooperation Characters - Rahmawati, Mina Laili; Utomo, Arief Cahyo (Jurnal Elementaria Edukasia, 2025)
This study aims to analyze the process of implementing volleyball extracurricular activities in fostering the character of discipline and mutual cooperation and describe the methods, supporting factors, and inhibitors of growing the character of discipline and mutual cooperation in volleyball extracurricular activities at SD Negeri 1 Bulurejo. Researchers used data collection methods of observation, interviews, and documentation. The observation used in this research is a type of passive participation observation. Researchers conducted semi-structured interviews. The documentation in this study includes school profiles, student lists, and volleyball extracurricular assessment sheets. Researchers used data triangulation in the form of source triangulation and technique triangulation. This research uses 3 stages of data analysis techniques, namely data reduction, data presentation, and conclusion drawing. The results showed that the characters of discipline and mutual cooperation were internalized in the process of implementing volleyball extracurricular activities such as students coming to the training ground on time, obeying all the rules when practicing volleyball, working together when practicing, sharing information, and helping each other. The methods used to foster the character of discipline and mutual cooperation are the habituation method and the exemplary method. Supporting factors for the growth of discipline and mutual cooperation characters are students' interest and motivation when participating in volleyball training, while the inhibiting factors are weather factors and students self-awareness to behave in a disciplined and mutual cooperation.